2016
DOI: 10.1111/hdi.12446
|View full text |Cite
|
Sign up to set email alerts
|

Predialysis volume overload and patient‐reported sleep duration and quality in patients receiving hemodialysis

Abstract: Hydration status was associated with self-reported sleep duration in patients on dialysis. Future studies should prospectively examine the effects of optimizing fluid status on sleep duration and quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…Other disorders with potential for volume overload such as end‐stage renal disease have found self‐reported fatigue to be associated with an extracellular water excess 37 . Similarly, increased volume status was associated with fewer hours of sleep and more frequent nighttime awakenings in dialysis patients 38 . Elevated right atrial pressures appear to coincide with an increase in dyspnea, fatigue, and sleep disturbance in PAH, which could be explained by cardiorenal or cardiohepatic syndromes.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Other disorders with potential for volume overload such as end‐stage renal disease have found self‐reported fatigue to be associated with an extracellular water excess 37 . Similarly, increased volume status was associated with fewer hours of sleep and more frequent nighttime awakenings in dialysis patients 38 . Elevated right atrial pressures appear to coincide with an increase in dyspnea, fatigue, and sleep disturbance in PAH, which could be explained by cardiorenal or cardiohepatic syndromes.…”
Section: Discussionmentioning
confidence: 96%
“…37 Similarly, increased volume status was associated with fewer hours of sleep and more frequent nighttime awakenings in dialysis patients. 38 Elevated right atrial pressures appear to coincide with an increase in dyspnea, fatigue, and sleep disturbance in PAH, which could be explained by cardiorenal or cardiohepatic syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to OSA, only one previous study has examined the relationship between volume overload and sleep quality of the HD population. Abreo and his colleagues [10] reported a negative association between the predialysis volume status measured through BIA and the sleep duration of HD patients. However, a causal relationship was not confirmed, since no intervention was performed.…”
Section: Discussionmentioning
confidence: 99%
“…A previously conducted study reported an improvement regarding sleep apnoea with the help of nocturnal HD [9], which places emphasis on the role played by excess fluid in case of sleep disorders. Furthermore, a recent study reported that an increase in predialysis volume status measured with bioelectrical impedance analysis (BIA) was associated with fewer hours of sleep [10], which leads to the concept of sleep quality improvement with better volume control in chronic HD patients.…”
Section: Introductionmentioning
confidence: 99%
“…A study of 638 HD patients found that both mild ( N = 149) and substantial ( N = 337) volume overload by bioimpedence were associated with an adjusted 1.9 fold higher risk of frequent nighttime awakenings as well as fewer hours of sleep …”
mentioning
confidence: 99%